Cost Effectiveness of Transbronchial Needle Aspiration - Jennifer A Crocket; Eric YL Wong; Dale C Lien; Khanh Gia Nguyen; Michelle R Chaput; Ciaran McNamee (Canadian Respiratory Journal)
OBJECTIVE: To evaluate the yield and cost effectiveness of transbronchial needle aspiration (TBNA) in the assessment of mediastinal and/or hilar lymphadenopathy.